Entrepreneurial Capacity Melalui Pengembangan Produk UMKM Shafah Berbahan Dasar Singkong Sebagai PKM Kewirausahaan Desa Bulakan Kota Cilegon - Hafidz Hanafiah; Juhandi Juhandi; Ismi Azalika Ummah; Nungki Agustin; Yunica Marsha Sagina (Jurnal Informasi Pengabdian Masyarakat, 2024)
Entrepreneurial capacity or entrepreneurial capacity is the entrepreneurship possessed by business actors in seeing potential or opportunities to become economic value. The aim of this PKM in the field of entrepreneurship is to develop cassava MSME products using the entrepreneurial capacity model. The method for implementing this PKM by KKM 42 students at Bina Bangsa University, Bulakan Village, was used through surveys, discussions, implementation and evaluation. The results of this PKM in the field of entrepreneurship show the potential for Shafah MSME products made from cassava to be developed using the entrepreneurial capacity model, not only that, the production volume of this MSME product can also be expanded by adding human resources and machines.